Intake, digestibility and growth of roaster rabbits fed graded dietary levels of neem (Azadirachta indica) seed kernel-cake - VASANTHAKUMAR, P; SHARMA, K; SASTRY, V B R (The Indian Journal of Animal Sciences, 2013)
Male broiler rabbits (24) of 12-week-old were assigned equally to 4 isonitrogenous and isocaloric composite (25 roughage: 75 concentrate) dicts containing 0 (D1), 5 (D2), 10(D3) and 20 (D4)% neem seed kernal-cake (NSKC), fed ad lib up to 24 weeks of age. The intake and digestibility of most of the nutrients and retention of nitrogen and energy depressed with Increasing dietary levels of NSKC. The nutritive value of diets having NSKC beyond 10% was lower than the diets containing deoiled groundnut-cake and 5% NSKC. However, the rabbits on all the diets grew without any significant difference with similar efficiency of nutrient utilization (unit intake/unit gain). Incorporation of NSKC at higher dietary levels for longer periods appears to affect the nutritional performance of roaster rabbits adversely.